Efficacy comparison of toripalimab versus pembrolizumab in neoadjuvant treatment of breast cancer: impact of chemotherapy regimen and sequence on pathologic complete response - Zhang, Yunjiao; Zhang, Bo; Chen, Xi; Zhang, Xue; Liu, Chutuo; Wang, Zhe; Ling, Rui (Frontiers in Oncology, 2025)
ObjectiveThis real-world study aimed to compare the efficacy and safety of the domestically developed PD-1 inhibitor toripalimab with pembrolizumab in the neoadjuvant treatment of breast cancer, and to further investigate the impact of treatment cycles, platinum-based chemotherapy, and chemotherapy sequencing on pathologic complete response (pCR).MethodsThis retrospective study included 114 breast cancer patients who received neoadjuvant therapy with either toripalimab or pembrolizumab at the First Affiliated Hospital of Air Force Medical University between January 2021 and January 2025. Participants were stratified into groups based on: (1) immunotherapy cycles (completed 8 cycles vs. incomplete); (2) chemotherapy regimen (platinum vs. non-platinum); (3) chemotherapy sequence (EC-T, EC-TCb, T-EC, TCb-EC, or other); and (4) PD-1 inhibitor type (toripalimab vs. pembrolizumab). The primary endpoint was total pCR (tpCR; ypT0/is ypN0). Secondary endpoints included breast pCR (bpCR) and residual cancer burden (RCB). Statistical analyses incorporated Chi-square tests and Fisher’s exact tests for group comparisons. Baseline characteristics were compared across groups to assess the potential for confounding.ResultsNo significant differences were observed in tpCR (56.7% vs. 46.8%; P=0.297) or RCB-0 rates (56.7% vs. 44.7%; P=0.524) between patients completing versus not completing 8 immunotherapy cycles. The tpCR rate did not differ significantly between platinum-based and non-platinum-based regimens (53.6% vs. 51.7%, P=0.843). Chemotherapy sequence significantly affected efficacy: the TCb-EC group achieved the highest tpCR rate (79.2%), significantly outperforming EC-T (56.4%) and other regimens (27.3%). Toripalimab and pembrolizumab showed no significant difference in tpCR rate (56.8% vs. 50.0%, P=0.777) or RCB-0 rate (56.8% vs. 48.6%, P=0.903).ConclusionToripalimab demonstrated non-inferior efficacy compared to pembrolizumab in the neoadjuvant treatment of breast cancer. Chemotherapy sequence—particularly the TCb-EC regimen—significantly predicted pCR, while immunotherapy cycle number and platinum use did not influence pathologic outcomes. These real-world findings support toripalimab’s clinical use and underscore the importance of optimizing chemoimmunotherapy sequencing.